Quantitative Easing and Economic Stimulus Policies: Potential Benefiting from Them in Iraq - Kadhim, Halah Hashim; Dakhel, Alaa Abbas (Research Parks Publishers, 2025)
Quantitative easing is an unconventional monetary policy used by some central banks to stimulate the local economy. The central bank prints a predetermined amount of money that will be used to purchase government bonds or financial assets to increase liquidity, this increases the excess reserves of the banking system, increases the prices of the financial assets that were purchased, and reduces their size. Banks are also forced to lower the interest rate, which leads to increased borrowing in the country and thus stimulates the economy. This policy is usually used when normal methods of controlling the money supply fail, that is, when the bank interest rate, discount rate, and interbank interest rate are at or near zero. Through its mandate, the Central Bank of Iraq seeks to support the development process and stimulate economic growth in Iraq by supporting the liquidity of specialized banks with financial initiatives that enable them to provide industrial, agricultural, and housing loans to support economic activity and create job opportunities. It also provides financial initiatives to private commercial banks to finance small and medium-sized enterprises, the bank has taken several steps and provided facilities, including banking facilities through rescheduling bank loans to the private sector, particularly those owed by small and medium-sized enterprises, as well as extending the repayment period for existing and future loans , Continuing to support real activities through the lending policy adopted by the Central Bank and in cooperation with banks operating in Iraq to drive development.